The Tyranny Of The Majority : Fundamental Fairness in Representative Democracy - Guinier, Lani (Free Press, 1995)
In her new book, The Tyranny of the Majority, Lani Guinier offers a powerful, principled critique of American democracy. She argues for a standard of fundamental fairness in comparison to which the current electoral and legislative systems are procedurally unfair. Guinier's standard of fundamental fairness requires that every contestant have an equal chance of winning each contest. Winner-take-all rules, single-member district races, and simple majority legislative decisions all increase the likelihood that some participant will win at the expense of others. After demonstrating that these systems violate the principle of fundamental fairness, Guinier proposes remedial measures meant to cure the inequities they produce. The principled application of the primary remedial measure Guinier suggests, cumulative voting, offers opportunities for dramatic change in the American political system. Unfortunately, Guinier never explores the full extent of these opportunities.